Game-Theoretic Approach to Bank Loan Repayment - Paliński, Andrzej (Decision Making in Manufacturing and Services, 2016)
The paper presents a model of a bank loan repayment as a signaling game with a set of discrete types of borrowers. The type of the borrower is the return on investment project. A possibility of renegotiation of the loan agreement leads to an equilibrium in which the borrower adjusts repaid amount to the liquidation value of its assets from the bank’s point of view. In the equilibrium there are numerous pooling equilibrium points with values rising according to the expected liquidation value of the loan. The article additionally proposes mechanism forcing the borrower to pay all of his return instead of the common liquidation value of subset of types of the borrower. The paper contains also a simple numerical example explaining this mechanism.